REPRESENTATION AND SUBSTANTIVE REPRESENTATION OF WOMEN IN THE 2024 PILKADA CITY OF PALU - Muthia (Musawa: Journal for Gender Studies, 2025)
This research aims to analyze the representation and substantive representation of women in local political contests, especially in the 2024 Regional Elections in Palu City. Women's representation in politics has been dominated by quantitative approaches, while the substantive dimension the extent to which women are able to fight for strategic issues and gender needs in public policy is often overlooked. This research uses a qualitative approach with a case study design, with data collection techniques in the form of in-depth interviews, participatory observations, and analysis of campaign documents and political party policies. The results of the study show that women's representation in the 2024 Regional Elections is still numerically low, with only a few female candidates appearing in the regional head nomination exchange. The main inhibiting factors for women's political participation include economic barriers, patriarchal cultural stereotypes, lack of support from political institutions, and the burden of domestic roles. However, the study also found that there is a form of substantive representation that is beginning to develop, characterized by women's involvement in community-based campaigns, organizing social issues, and non-traditional electoral strategies rooted in local social networks. This study recommends the importance of internal political party reforms, strengthening women's political capacity, and gender-based political education at the grassroots level to encourage women's meaningful involvement in local political processes.